(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
Education is an on-going effort towards further developing a nation in term of human capital investment and returns. Recent economic figures clearly show that, countries with better-educated workforce tend to have higher income, lower poverty rate and slower rate of population growth. Generally, education plays an important role in term of earnings and able to creates earnings discrimination among workers. This study attempts to investigate the private rate of returns for business and management graduates in Malaysia using cost and benefit analysis. In this study, data collection is based on random sampling conducted through the business and management graduates alumni division. The overall findings clearly indicate positive returns on education for male and female management graduate with an average of 15-30 percentages.